Shifting foundations: the mechanical cell wall and development. (February 2016) - Braybrook, Siobhan A; Jönsson, Henrik
Graphical abstract: Highlights: Recent experiments and modelling which have advance wall mechanics are described. A need for understanding growth mechanics within 3D contexts is raised. A call for multi-scale modelling to describe complexities at all biological levels. Some future directions for experiments and modelling are proposed. Abstract : The cell wall has long been acknowledged as an important physical mediator of growth in plants. Recent experimental and modelling work has brought the importance of cell wall mechanics into the forefront again. These data have challenged existing dogmas that relate cell wall structure to cell/organ growth, that uncouple elasticity from extensibility, and those which treat the cell wall as a passive and non-stressed material. Within this review we describe experiments and models which have changed the ways in which we view the mechanical cell wall, leading to new hypotheses and research avenues. It has become increasingly apparent that while we often wish to simplify our systems, we now require more complex multi-scale experiments and models in order to gain further insight into growth mechanics. We are currently experiencing an exciting and challenging shift in the foundations of our understanding of cell wall mechanics in growth and development.